Hyperamylazémie, laboratorní a klinické aspekty - Kocna, P; Zima, T (Casopis lekaru ceskych, 2006)
Biochemical estimation of the total a-amylase represents in the Czech Republic almost two millions of assessments per year. Estimation of the total alpha-amylase for the diagnostics of pancreatic diseases has a very low specificity and it is therefore recommended to analyze specific pancreatic enzymes - pancreatic isoenzyme alpha-amylase and pancreatic lipase. Paper summarizes laboratory and clinical aspects aimed namely on hyperamylasamia.
Keywords: izoenzymy; alpha-Amylases; senzitivita a specificita; lidé; Sensitivity and Specificity; Isoenzymes; alfa-amylasy; Biomarkers; Lipase; biologické markery; Humans; Hyperamylasemia; lipasa; hyperamylazemie